2023
DOI: 10.3389/fphar.2023.1179208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of elexacaftor/tezacaftor/ivacaftor therapy on mental health of patients with cystic fibrosis

Abstract: Introduction: The CFTR modulator drug elexacaftor/tezacaftor/ivacaftor (ETI) was shown to improve CFTR function and clinical symptoms in patients with cystic fibrosis (CF) with at least one F508del allele. Recently, some case reports suggested potential side effects of ETI on mental health with an increase in depressive symptoms and even suicide attempts in patients with CF. However, the general effects of this triple combination therapy on the mental health status of patients with CF remain largely unknown.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…These studies, which involved 951 pwCF and reflected real-world experiences with up to 12 months of follow-up, did not indicate any systematic increases (i.e., worsening) in PHQ-9 scores on average, demonstrating either no change or a decrease (i.e., improvement) in assessed PHQ-9 (or PHQ-8) scores after ELX/TEZ/IVA initiation ( Table 3 ). Notably, one of those studies, a prospective observational cohort of 70 adults with CF treated with ELX/TEZ/IVA in Germany, reported a trend toward a decrease in patients describing suicidal ideation: Before therapy initiation, four patients (5.6%) reported suicidal ideation on the PHQ-9, and after therapy initiation, only one patient (1.4%) reported suicidal ideation ( 33 ). One additional study of 84 adults with CF reported no significant change in score on the Center for Epidemiologic Studies–Depression Scale after 6 months post ELX/TEZ/IVA initiation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, which involved 951 pwCF and reflected real-world experiences with up to 12 months of follow-up, did not indicate any systematic increases (i.e., worsening) in PHQ-9 scores on average, demonstrating either no change or a decrease (i.e., improvement) in assessed PHQ-9 (or PHQ-8) scores after ELX/TEZ/IVA initiation ( Table 3 ). Notably, one of those studies, a prospective observational cohort of 70 adults with CF treated with ELX/TEZ/IVA in Germany, reported a trend toward a decrease in patients describing suicidal ideation: Before therapy initiation, four patients (5.6%) reported suicidal ideation on the PHQ-9, and after therapy initiation, only one patient (1.4%) reported suicidal ideation ( 33 ). One additional study of 84 adults with CF reported no significant change in score on the Center for Epidemiologic Studies–Depression Scale after 6 months post ELX/TEZ/IVA initiation ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…As part of this review, we identified 12 published articles and congress presentations that utilized the well-validated PHQ-9 (or PHQ-8) to evaluate depression symptoms both before and after ELX/TEZ/IVA initiation in more than 951 pwCF ( 33 , 35 45 ). These studies found that, on average, PHQ-9 (or PHQ-8) scores either decreased (indicating an improvement in depression symptoms) or showed no change after ELX/TEZ/IVA initiation.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on ETI effects on depression and anxiety in PwCF evidences a general pattern reflecting increased quality of life for a majority, while a minority has new onset or worsened depression and/or anxiety. Piehler et al prospectively evaluated CF-related quality of life along with depression and anxiety in 70 adults with CF before and after initiation of ETI [ 12 ]. At the level of group statistics, this study showed that ETI improved CF-related quality of life, was associated with a very small but statistically significant improvement in median depression scores, and had no effect on median anxiety scores.…”
Section: The Scope Of the Problemmentioning
confidence: 99%
“…Borawska-Kowalczyk and colleagues ( 10 ) reported that although there was no overall change in PHQ-9 score, 15% of pwCF had increased scores after ELX/TEZ/IVA initiation. Piehler and colleagues ( 11 ) demonstrated clearly that although overall the group showed reduction in depression symptoms as measured by PHQ-9, there was certainly a proportion of subjects who had worse PHQ-9 scores after commencing ELX/TEZ/IVA therapy; indeed PHQ-9 score increased by 17% in the group with minimal depression symptoms at baseline ( see Figure 1 ).…”
mentioning
confidence: 96%
“…**Denotes P < 0.01 compared with baseline. Reprinted by permission from Reference 11 . ELX = elexacaftor; ETI = elexacaftor/tezacaftor/ivacaftor; IVA = ivacaftor; TEZ = tezacaftor.…”
mentioning
confidence: 99%